2015
DOI: 10.1093/nar/gkv1063
|View full text |Cite
|
Sign up to set email alerts
|

H3K23me2 is a new heterochromatic mark inCaenorhabditis elegans

Abstract: Genome-wide analyses in Caenorhabditis elegans show that post-translational modifications (PTMs) of histones are evolutionary conserved and distributed along functionally distinct genomic domains. However, a global profile of PTMs and their co-occurrence on the same histone tail has not been described in this organism. We used mass spectrometry based middle-down proteomics to analyze histone H3 N-terminal tails from C. elegans embryos for the presence, the relative abundance and the potential cross-talk of co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 80 publications
3
46
0
Order By: Relevance
“…PHF8 shares high homology with the C. elegans JMJD-1.2 protein, which retains both the JmjC and the PHD finger domains. However, the catalytic activity of JMJD-1.2 appears to differ from that of the mammalian counterpart, as several studies have shown its ability to demethylate not only H3K9me2, but also H3K27me2 and H3K23me2, both in vitro and in vivo (Kleine-Kohlbrecher et al, 2010;Lin et al, 2010;Vandamme et al, 2015). In agreement with the role of PHF8 in neuronal processes, JMJD-1.2 is required for normal locomotion in C. elegans, highlighting the importance of this protein in the establishment of neuronal functionalities (Kleine-Kohlbrecher et al, 2010).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…PHF8 shares high homology with the C. elegans JMJD-1.2 protein, which retains both the JmjC and the PHD finger domains. However, the catalytic activity of JMJD-1.2 appears to differ from that of the mammalian counterpart, as several studies have shown its ability to demethylate not only H3K9me2, but also H3K27me2 and H3K23me2, both in vitro and in vivo (Kleine-Kohlbrecher et al, 2010;Lin et al, 2010;Vandamme et al, 2015). In agreement with the role of PHF8 in neuronal processes, JMJD-1.2 is required for normal locomotion in C. elegans, highlighting the importance of this protein in the establishment of neuronal functionalities (Kleine-Kohlbrecher et al, 2010).…”
Section: Introductionmentioning
confidence: 69%
“…The JmjC domain of JMJD-1.2 has been shown to demethylate H3K9me2, H3K27me2 and H3K23me2 in vitro and in vivo and, accordingly, increased signal of these post-translational modifications is found in the tm3713 mutant strain (KleineKohlbrecher et al, 2010;Lin et al, 2010;Vandamme et al, 2015). To test the relevance of JMJD-1.2 enzymatic activity in axon guidance, we mutated the JmjC domain (Fig.…”
Section: Research Articlementioning
confidence: 99%
“…An intriguing possibility is that a recently discovered mark, H3K23me3, which is strongly enriched in the germline of both Tetrahymena and C. elegans , may play a more direct role in repressing DSB formation by SPO-11 [28]. While the genome-wide distribution of this mark in C. elegans has not yet been reported, and nothing is yet known about its regulation, H3K23me3 has been found to be co-enriched on H3 tails that also carry H3K9me2 or H3K9me3 [29]. …”
Section: The Landscape Of Dsbs Underlies the Crossover Distribution Imentioning
confidence: 99%
“…The presence of H3K23me2 in C. elegans has been shown to correlate with regions that have H3K9me3 and heterochromatic regions (Vandamme et al, 2015). However, information on mammalian cells is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Although the functions of many histone modifications have been elucidated, many still remain to be resolved. In general, the modifications H3K9me3, H2K9me, H3K27me2 and H3K27me3, as well as the recently described H3K23me2 (Vandamme et al, 2015), are associated with transcriptional silencing and formation of heterochromatin (Bannister and Kouzarides, 2011). The modifications associated with transcription activation are H3K4me3, H4K2me, H3K9Ac, H3K36me3 and H4K5Ac (Harr et al, 2016).…”
Section: Introductionmentioning
confidence: 97%